Synthesis and pharmacological evaluation of new fluorine substituted pyrimido[1,2-b][1,2,4]triazines and [1,3,5]-triazino-[1,2-b][1,2,4]triazines derived as CDK2 potential inhibitors - Bakhotmah, Dina; Alotaibi, Fatimah (European Journal of Chemistry, 2020)
New fluorine-substituted polyfunctional pyrimido-[1,2-b]-[1,2,4]triazines and [1,3,5]-triazino[1,2-b]-[1,2,4]triazines were synthesized via the reaction between 3-amino-6-(2-aminophenyl)-1,2,4-triazin-5(2H)-one with polyfunctional oxygen/sulfur/nitrogen reagents under different conditions. Structures of the target compounds were deduced by elemental analysis and spectral measurements (IR, 1H/13C NMR, and mass spectra). According to the obtained inhibitor assay results, the inhibition activity of the new fluorine-substituted 1,2,4-triazines toward CDK2 decreased in the order of compounds 3 > 8 > 9 > 6 > 13 > 15.